Physical rehabilitation of women after mastectomy - Korabiusz, Katarzyna; Wawryków, Agata; Torbé, Dorota; Janik, Inga; Torbé, Andrzej (Journal of Education, Health and Sport, 2017)
Introduction: Breast cancer is one of the most frequent causes of death amongst women in Poland. This is why it is so important to minimize complications that occur after oncological treatment. Rehabilitation process is long and complex and rehabilitation should include psychological as well as physical area. Patients mostly suffer from lymphatic swellings of upper limbs on the side that was operated, pain and reduction in range of movement in shoulder joint. Goal of dissertation: Goal of this dissertation is a review of literature about available physiotherapy methods used in women following mastectomy. Conclusion: There are many physiotherapy methods used in women following mastectomy that improve their quality of life. Methods proposed in literature decrease lymphatic swelling of upper limb on operated side. They also increase range of movement in shoulder joint and reduce pain. The most often used methods are: manual and mechanical lymphatic drainage, self-massage, scar work, transdermal nerves stimulation TENS , kinesitherapy (individual as well as group exercises such as nordic walking, yoga, music therapy, choreotherapy, group gymnastics) and anti-swelling kinesiotaping.